Life design counselling with a learner from a vocational school setting - Ruiters, S-E.; Maree, J. G. (South African Journal of Higher Education, 2022)
This article reports on the usefulness of life design counselling for a learner from a vocational school (learner with intellectual impairment) when making post school decisions. Vocational and/or career research and reporting on people with intellectual disability/impairment, especially in the South African education context, is limited and infrequent. A purposively sampled, single, intervention case study was utilised. Data generation and analysis were approached simultaneously. The intervention uncovered career/vocational themes significant to the participant. These themes highlighted the meaning he attributed to work and his role and purpose in the world of work. The intervention also proved effective in cultivating his self- and career-efficacy and adaptability. Post intervention, the participant more confidently pursued his passion and was able to identify and utilise resources more definitely. Further, longitudinal research with groups of people with different kinds of impairment from vocational school settings is needed to further examine the value of the intervention described here.